Moving Beyond the Device: Key Lessons in Creating a Positive Patient Experience for a Remote Foot Health Program - Gary M. Rothenberg DPM, CDCES, CWS; Jordan Munson RN, MSN; Ezra Josephson BA, MBA; Jon Bloom MD (Journal of Patient Experience)
The burden of diabetic foot ulcers is largely underappreciated, even by the healthcare community. Living with advanced, complex chronic diseases can be challenging for the patient and often requires additional time and resource utilization by the provider. The use of novel technology within medicine should be focused on fostering excellent experiences, thereby promoting satisfaction and ultimately, quality care. Using a remote foot temperature monitoring program, we have learned that 3 strategies support positive experience including: design for ease of use, patient and provider support, and continuous process improvement. Further key points include: (1) foot ulcers and amputations are a significant source of morbidity, mortality, and decreased quality of life for people living with diabetes; (2) remote patient monitoring innovations in technology can help connect patients, healthcare providers, and data; (3) technology should serve as an extension of the patient–provider trust relationship and help improve systemic efficiency; and (4) future considerations for successful patient experiences must also address healthcare disparities and promote health equity.